2017
DOI: 10.5713/ajas.17.0145
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity, major genes and production potential of local chickens and guinea fowl in Tamale, northern Ghana

Abstract: ObjectiveOur study provides information on phenotypes of local chickens and guinea fowl and their body measures as well as on major genes in local chickens in northern Ghana.MethodsQualitative and morphometric traits were recorded on 788 local chickens and 394 guinea fowl in urban households in Tamale, Ghana.ResultsThe results showed considerable variation of color traits and numerous major genes in local chickens, while color variations and related genotypes in guinea fowl were limited. In local chickens, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
23
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 11 publications
13
23
5
3
Order By: Relevance
“…The mean value for body weight observed in this study was higher than the values 1.23 g, 1.13 g and 1.28 g for pearl grey, peal grey pied and white guinea fowls in Ghana reported by Brown et al [17]. This could be that the French broiler guinea fowl is an improved strain compared to pearl grey, peal grey pied and white guinea fowls.…”
Section: Body Weight and Body Linear Parametercontrasting
confidence: 84%
See 1 more Smart Citation
“…The mean value for body weight observed in this study was higher than the values 1.23 g, 1.13 g and 1.28 g for pearl grey, peal grey pied and white guinea fowls in Ghana reported by Brown et al [17]. This could be that the French broiler guinea fowl is an improved strain compared to pearl grey, peal grey pied and white guinea fowls.…”
Section: Body Weight and Body Linear Parametercontrasting
confidence: 84%
“…Mean shank length observed in this study was also higher than the value reported by Kasperska et al [18] but lower than the range of 8.88 ± 3.1 cm to 9.31 ± 4.7 cm reported by Panyoka et al [19] for domestic and wild helmeted guinea fowl of Kenya. Brown et al [17] also reported higher values for local guinea fowl in Ghana. Differences observed in this study could be attributed to differences in breeds, levels of improvement, environmental factors and management practices body linear parameters, indicated by the prediction equations showed that, the predictive equations could be used to predict body weight with high accuracy.…”
Section: Body Weight and Body Linear Parametermentioning
confidence: 91%
“…Knowledge of trait preferences for breeding decisions is central to the formulation of livestock policies aimed at improving the livelihoods of smallholder chicken farmers. Evaluation of trait preferences of local poultry producers is required for the design of appropriate breeding programs (Brown et al 2017). This may be particularly indispensable under the free scavenging production system (Markos et al 2016), where the economic weights of traits could be difficult to calculate and also permit the inclusion of non-market traits in the economic valuation of the chicken (Bett et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that red is the predominant color for eyes of male Pelung chickens, while yellow and black are minor. The three eye colors were also stated by Brown et al (2017), who characterized local chickens in Ghana. Two types of melanin, eumelanin (responsible for brown/black color) and pheomelanin (responsible for yellow/red color), synthesize the eye pigmentation (Steven 1991).…”
Section: Discussionmentioning
confidence: 82%
“…The red color of iris in male chickens is more intense than that in female chickens as red blood cells in male chickens are greater than in female (Corti and Vogelaar 2010). Red eyes were more frequent in cocks than in hens of local chickens in Ghana (Brown et al 2017).…”
Section: Discussionmentioning
confidence: 93%